Role of microbiota-gut-brain axis in natural aging-related alterations in behavior - Jing, Yingli; Wang, Qiuying; Bai, Fan; Li, Zihan; Li, Yan; Liu, Weijin; Yan, Yitong; Zhang, Shuangyue; Gao, Chen; Yu, Yan (Frontiers in Neuroscience, 2024)
Ageing is a complex, time-dependent biological process that involves a decline of overall function.Over the past decade, the field of intestinal microbiota associated with ageing has received considerable attention. However, there is limited information surrounding microbiota-gut-brain axis (MGBA) to further reveal the mechanism of ageing. In this study, decreased locomotor activity, decreased pain sensitivity, and reduced respiratory metabolic profiling were observed in aged mice.High-throughput sequencing revealed that the levels of genus Lactobacillus and Dubosiella were reduced, and the levels of genus Alistipes and Bacteroides were increased in aged mice. Certain bacterial genus were directly associated with the decline of physiological behaviors in aged mice.Furthermore, the amount of fecal short-chain fatty acids (SCFAs) in aged mice was decreased, accompanied by an upregulation in the circulating pro-inflammatory cytokines and increased expression of inflammatory factors in the brain. Ageing-induced microbial dysbiosis was closely related with the overall decline in behavior, which may attribute to the changes in metabolic products eg SCFAs, caused by an alteration in the gut microbiota, leading to inflammaging and contributing to neurological deficits. Investigating the MGBA might provide a novel viewpoint to exploring the pathogenesis of ageing and expanding appropriate therapeutic targets.